Relationship Between Knowledge, Infrastructure and Work Stress Towards Nurses' Compliance in Implementing Discharge Planning in Stroke Patients - Anggraini, Retno; Sajidin, Muhammad; Azizah, Lilik Ma’rifatul; Lestari, Indah; Maryam, Dewi (GLOBAL HEALTH SCIENCE GROUP, 2024)
Stroke is a disease of the blood vessels of the brain that can occur due to blockage or rupture of blood vessels in the brain, causing cell death. Stroke requires comprehensive care so that the family plays an important role in helping the patient recover after the acute phase has passed. Therefore, providing optimal discharge planning by health workers greatly helps patients and families in providing care at home. Objective to analyze the factors of knowledge, facilities and infrastructure and work stress on nurses' compliance in providing discharge planning. This study used a cross-section design with a sample of 80 nurses. Data collection using a questionnaire included independent variables in the form of knowledge, facilities and infrastructure and work stress and dependent variables in the form of nurse compliance. This questionnaire has been previously tested by researchers to 30 respondents. Data were analyzed using logistic regression with a p value ≤ 0.05. The results showed that there was an influence between knowledge (0.004), facilities and infrastructure (0.015), and work stress (0.017) on nurse compliance in implementing discharge planning in stroke patients. The factors of knowledge, facilities and infrastructure and work stress have a significant influence on nurse compliance in implementing discharge planning in stroke patients. Therefore, nursing managers should facilitate the provision of health education regarding discharge planning to nurses and routinely carry out nursing supervision to increase nurse compliance.